Intuitive Intelligence for teams and organisations - Subiah R., Manj (Henry Stewart Talks, 2020)
Strategy, power decision making paradigm, Organisational structure, Intuitive intelligence for teams in the organisation, Organisational cultural behavioural context, Resources and capabilities in the organisation